Tailoring Acoustic Performances of Resin Reinforced Biomass Fiber-Based Panel with Single and Multiple Tailed Cavity Inclusions for Interior Work - Erni Setyowati; Gagoek Hardiman; Purwanto Purwanto (Fibers, 2019)
The aim of this research is to observe the acoustic performance of absorber-based biomass fiber-reinforced polyester resins that were experimentally associated with the design of tailed cavity resonator inclusion, i.e., the cavities are partly in the form of a narrow slit. The model of electro-acoustic resonators and several treatments were developed and became the bases for understanding the changes of acoustic reactance in the new structure. Variations in the inclusion cavity and the addition of a narrow slit were tested experimentally using an impedance tube technique based on ASTM E1050-98 and ASTM E2611-09. The improvements of acoustic performance were conducted by single and multiple cavity tailed inclusions with the addition of a Dacron fibrous layer and back cavity. The experimental results showed that a sample of 15 mm single tailed cavity kenaf fiber had higher sound absorption and wider broadband frequencies than did the hemp fiber, with a peak on 0.31−0.32 between 1.00−2.00 kHz. Meanwhile on multiple tailed cavities, the 30 mm hemp fiber had higher and wider broadband frequencies than did the kenaf, with peaks on 0.45−0.63 at frequencies between 1.75−2.10 kHz. It can be concluded that the tailed cavity inclusions could improve performance. Compared to the coco-husk with resonators in previous studies, the tailed cavity was a little bit lower, but the tailed cavities hemps and kenafs samples showed good sound absorption performance with lower band frequencies capabilities.